Study the Teacher Empowerment in reference to Administrative Behaviour of School Heads working in Rural and Urban Schools - Pathak, Priya; Goswami, Dr.Vandana (IJRDO-Journal of Applied Science, 2015)
With the liberalization and the globalization of the Indian economy, the rapidchanges witnessed in the scientific and technological world, and it is realized that the emergingIndian society can achieve all round development with the help of the teachers who act as apowerful agency in transmitting its cherished values. So here an empowered teacher is thenecessity of the society. The objective was to study the Teacher Empowerment in reference toAdministrative Behaviour of School Heads working in Rural and Urban schools. The sampleof this study comprises 48 Heads, 405 teachers from different senior secondary (10+2) Ruraland Urban schools of Agra division (U. P.). For measuring Administrative Behaviour of SchoolHeads, Administrative Behaviour scale developed by Dr. Haseen Taj in 1998 was used andTeacher Empowerment scale was prepared by the researcher. The finding of this study statesthat differences found in Teacher Empowerment of Rural and Urban school teachers inreference to their Administrative Behaviour of School Heads.